The neuronal and synaptic representations of spatial release from masking in the rat auditory cortex - Chen, Guanhua; Zhang, Jiping (Frontiers in Neuroscience, 2025)
In complex acoustic environments, both humans and animals are frequently exposed to sounds from multiple sources. The detection threshold for a target sound (or probe) can be elevated by interference sounds (masker) originating from various locations. This masking effect is reduced when the probe and masker are spatially separated compared to when they are colocalized, thereby improving the perception of the probe. This phenomenon is known as spatial release from masking. Currently, the neuronal and synaptic mechanisms underlying spatial release from masking in the auditory cortex are not fully understood. Here we employed single-unit recording and in vivo whole-cell patch-clamp recording techniques to examine how maskers from different spatial locations influence the detection thresholds of rat primary auditory cortex (A1) neurons in response to probe stimuli. At the cortical neuronal level, the masked detection thresholds of most A1 neurons in response to probes were significantly decreased when maskers were displaced from azimuths colocalized with the probe to other separated azimuths ipsilateral to the recording site. Similarly, at the cortical synaptic level, the masked detection thresholds of A1 neurons, as determined from the amplitude of evoked excitatory postsynaptic currents in response to probes presented at azimuth locations within the contralateral hemifield, were also decreased when maskers were shifted from azimuth locations in the contralteral hemifield to those in the ipsilateral hemifield. This study provides neuronal and synaptic evidences for spatial release from masking in the auditory cortex, advancing our understanding of the mechanisms involved in auditory signal processing in noisy environments.